Construction of Moral Value and Depiction of Indonesian-Chinese Folktale in Keong Mas Story - Tri Wahyu Retno Ningsih; Lu Li Qian Qian; Hukmawati Hukmawati (Indonesian Language Education and Literature, 2024)
One way to construct moral values in children is through stories. The purpose of this study is to find the construction of moral values with different cultural backgrounds in the Indonesian and Chinese versions of the Keong Mas story. The method that used in this research is a qualitative descriptive approach using literature and documentation studies. The data source is the Indonesian-Chinese version of the Keong Mas story. The results showed that the structural analysis in the two Keong Mas stories have a high degree of similarity. This similarity can be seen in the themes, characters and characterizations, plot, and mandate. The theme of the story of Keong Mas is courage, patience and courage. The main characters are a girl and a young man. The difference can be found in the settings. In the Indonesian version of the story it is set in a village, a forest edge, at home, a river, and a palace, while the Chinese version of the story is set in a village, on the side of a road around rice fields, at home, without bringing up a royal setting at all. The Indonesian and Chinese versions of the Keong Mas story construct moral values through themes which are fortitude and the mandate that a person must always do good things and strive so that his desires can be achieved.Konstruksi Nilai Moral dan Penggambaran Cerita Rakyat Indonesia-Tionghoa dalam Cerita Keong MasSalah satu cara untuk mengonstruksi nilai moral pada anak adalah melalui cerita. Tujuan penelitian ini adalah untuk menemukan konstruksi nilai moral yang berbeda latar belakang budaya dalam cerita Keong Mas versi Indonesia dan Tionghoa. Metode yang digunakan dalam penelitian ini adalah pendekatan deskriptif kualitatif dengan menggunakan studi literatur dan dokumentasi. Sumber datanya adalah cerita Keong Mas versi Indonesia-Tiongkok. Hasil penelitian menunjukkan bahwa analisis struktural pada kedua cerita Keong Mas mempunyai tingkat kemiripan yang tinggi. Kemiripan tersebut terlihat pada tema, tokoh dan penokohan, alur, serta amanat. Cerita Keong Mas versi Indonesia dan Tionghoa mengonstruksi nilai-nilai moral melalui tema-tema yang bersifat ketabahan dan amanah bahwa seseorang harus selalu berbuat baik dan berusaha agar keinginannya dapat tercapai.